1990
DOI: 10.1139/z90-041
|View full text |Cite
|
Sign up to set email alerts
|

Survival of radio-collared caribou (Rangifer tarandus caribou) from the George River herd, Nouveau-Québec – Labrador

Abstract: Between September 1983 and June 1987, 175 caribou (Rangifer tarandus caribou) from the George River caribou herd were captured and radio-collared. By October 1987, 42 of those had died: 15 were apparently killed by predators, 8 were legally shot, 4 appeared to have died proximally from malnutrition, 1 died from an accident, and cause of death could not be determined for 14 others. Seasonal and annual survival rates were estimated most precisely for adult (≥ 24 months) females, but a consistent trend towards lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…We inferred a death to have occurred when the satellite data indicated that a caribou had not moved for several days (Schaefer et al, 1999). Although evidence such as disarticulated carcasses, crushed long bones, or, if only the collar was retrieved, tooth marks or blood on the collar, indicated predation in some cases (Hearn et al, 1990;Schaefer et al, 1999), the long time interval between caribou death and collar retrieval precluded definitive identification of cause of death in several cases. Therefore, we consider here only deaths owing to harvest by humans and deaths assumed to be from natural causes (i.e., occurring far from human settlements and not associated with known hunting activities).…”
Section: Survivalmentioning
confidence: 99%
“…We inferred a death to have occurred when the satellite data indicated that a caribou had not moved for several days (Schaefer et al, 1999). Although evidence such as disarticulated carcasses, crushed long bones, or, if only the collar was retrieved, tooth marks or blood on the collar, indicated predation in some cases (Hearn et al, 1990;Schaefer et al, 1999), the long time interval between caribou death and collar retrieval precluded definitive identification of cause of death in several cases. Therefore, we consider here only deaths owing to harvest by humans and deaths assumed to be from natural causes (i.e., occurring far from human settlements and not associated with known hunting activities).…”
Section: Survivalmentioning
confidence: 99%
“…Caribou from the Riviere George herd have been equipped with radio collars since the autumn 1983 and monitored animals appear representative of the entire herd (Hearn et al 1990). Their location was determined a few days before photography.…”
Section: Proportion Of Females On Calving Grounds and Summer Survivalmentioning
confidence: 99%
“…The Rivière George caribou herd in northern Québec and Labrador increased at an annual rate of more than 10% in the period from 1954 to 1986, and seems to have stabilized at more than 680 000 individuals thereafter (Messier et al, 1988;Hearn et al, 1990;Couturier et al, 1996; situated on the tundra plateaus of the Rivière George (Messier et al, 1988;Crête et al, 1990a). For most North American ungulate species, winter habitats are normally more critical, in terms of forage availability and quality, than summer habitats (Messier et al, 1988).…”
Section: Introductionmentioning
confidence: 99%